2015
DOI: 10.1136/sextrans-2014-051952
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of sexually transmitted infections in pregnant adolescent girls in Tanzania: a multi-community cross-sectional study

Abstract: Background Limited data document sexually-transmitted infections (STIs) among pregnant adolescents in sub-Saharan Africa, where prenatal screening typically includes only HIV and syphilis. Given that HIV incidence in this population is among the world’s highest, we sought to assess the prevalence and factors associated with STIs in a population of rural pregnant adolescents in Tanzania. Methods We enrolled 403 pregnant adolescent girls from 10 antenatal clinics near Mwanza, Tanzania. Girls answered structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
5
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 26 publications
8
37
5
4
Order By: Relevance
“…This was significantly higher than prevalence among adolescent girls (p<0.001) in the same setting detected in a previous study 1. Moreover, CT was more strongly associated with primary (45/104, 43.3%) than with secondary (60/186, 32.2%) infertility.…”
contrasting
confidence: 56%
“…This was significantly higher than prevalence among adolescent girls (p<0.001) in the same setting detected in a previous study 1. Moreover, CT was more strongly associated with primary (45/104, 43.3%) than with secondary (60/186, 32.2%) infertility.…”
contrasting
confidence: 56%
“…This observation is also supported by previous study in Mwanza which showed that most of the women get pregnancy at young age indicating early sexual debut [22]. Additionally, recent study in Mwanza has shown significantly high prevalence rates of STIs among adolescents which may explain the increased risk of acquiring genital CMV [23].…”
Section: Discussionsupporting
confidence: 80%
“…This month, Becker et al report a study of concordance between child and adult reporting of HIV associated symptoms in South Africa 10. On a related note, we report the prevalence of STI among pregnant adolescents11 and mother to child HIV transmission 12. Other studies report on high levels of HPV in a rural population13 and on novel strains of chlamydia circulating in South Africa 14.…”
supporting
confidence: 56%